Dampak Pemekaran Daerah terhadap Struktur Ekonomi Kabupaten Hulu Sungai Utara dan Kabupaten Balangan - Ernawati Lipat Masan; M.Rusmin Nuryadin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
Generally, regional expansion is one form of local autonomy and is one of thepolicies that need to be considered due to regional growth, equitable regionaldevelopment, and regional development. It can be maximized. The purpose of this studywas to determine the impact of the Balangan Regency region expansion from the HuluSungai Utara Regency, whether with the division there was a shift in economicstructure in the two districts. Several analysis methods are used to answer the problem,namely: Location Quotient Analysis (LQ), Shift-Share Analysis, and Overlay Analysis.The data used in this study are secondary in the form of Hulu Sungai Utara RegencyGRDP, Balangan Regency GRDP, and South Kalimantan Province GRDP based onbusiness fields with the base year 2010. The study results based on Location Quotientanalysis show that the superior base sector in North Hulu Sungai Regency is parentdistricts are as many as 12 base sectors.In contrast, in the newly formed districts, there is only one base sector. Thecalculation result of Shift-Share analysis shows a shift in the two districts' economicstructure, namely from the primary industry to the secondary sector. The developmentof Overlay analysis indicates that there are ten leading sectors in the central districts,and in the newly created communities, there are no top sectors.